CO2 and H2S Absorption in Tofu Liquid Waste Biogas using Packed Bed Scrubber with Variation of MEA Concentration and Flow Rate - Putra, Aan Ade; Kalsum, Leila; Hasan, Abu (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Biogas technology has become an alternative fuel that is often used in Indonesia. One of the raw materials for biogas that has the potential and is easy to obtain is waste from the tofu industry. Liquid waste still contains a lot of organic elements. The organic materials contained in the exhaust of the tofu industry are generally very high. The gases commonly found in tofu waste are nitrogen gas (N2), oxygen (O2), hydrogen sulfide (H2S), ammonia (NH3), carbon dioxide (CO2) and methane (CH4). These gases come from the decomposition of organic materials contained in wastewater. So that biogas produced from tofu liquid waste still contains CO2 and H2S gases which are quite high. Therefore, in this study the process of purification or refining of biogas products will be carried out using the absorption method through an absorber column using monoethanolamine (MEA) solution as a chemical absorbent through a 8 mm packed bed scrubber. The results showed that the best biogas flow rate in the purification process which produced the highest CH4 concentration of 95.12% was 40% MEA concentration and 0.8 L/min flow rate. The effect of MEA concentration on biogas purification causes the concentration of CO2 and H2S in the purified biogas to decrease as the MEA concentration increases. The best combination of 0.8 L/min biogas flow rate and 10 mm packing area reduces CO2 and H2S concentrations to 1.88% and 0 ppm.